Impact of emphysema on the prognosis of Mycobacterium avium complex pulmonary disease. (February 2022) - Takasaka, Naoki; Hosaka, Yusuke; Fukuda, Taiki; Shinfuku, Kyota; Chida, Kentaro; Shibata, Shun; Kojima, Ayako; Hasegawa, Tsukasa; Yamada, Masami; Yamanaka, Yumie; Seki, Aya; Seki, Yoshitaka; et al.
Abstract: Background: Chronic obstructive pulmonary disease (COPD) is a major comorbid disease of Mycobacterium avium complex pulmonary disease (MAC-PD). Emphysema is one of the main pathological findings in COPD, a risk factor for chronic pulmonary aspergillosis (CPA), and is associated with poor prognosis. We aimed to clarify the effect of emphysema on mortality in MAC-PD. Methods: We retrospectively analyzed 203 patients with MAC-PD at The Jikei Daisan Hospital between January 2014 and December 2018. We investigated the mortality and CPA development rates after MAC-PD diagnosis in patients with or without emphysema. Results: Multivariate Cox proportional hazards regression analysis showed the following negative prognostic factors in patients with MAC-PD: emphysema (hazard ratio [HR]: 11.46; 95% confidence interval [CI]: 1.30–100.90; P  = 0.028); cavities (HR: 3.12; 95% CI: 1.22–7.94; P  = 0.017); and low body mass index (<18.5 kg/m 2 ) (HR: 4.62; 95% CI: 1.63–13.11; P  = 0.004). The mortality and occurrence of CPA were higher in MAC-PD patients with than without emphysema (log-rank test, P  < 0.0001 and P  < 0.0001). Conclusion: Our study findings showed that emphysema detected by computed tomography was associated with an increased risk of CPA development and mortality in MAC-PD. Highlights: Emphysema contributes to poor prognosis in MAC-PD. CPA development is a critical complication in MAC-PD with emphysema. Inhaled corticosteroid for COPD potentially contributes to MAC and CPA development.